Perencanaan Strategis Sistem Informasi Menggunakan Metodologi Ward and Peppard Pada Kantor Kecamatan Pusomaen - Manopo, Saliani Dewintari Agrytia; Latuperissa, Rudy (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
This research discusses Strategic Planning of Information Systems and Information Technology Using Ward and Peppard's Meteorology at the Pusomaen District Office. The Pusomaen District Office faces challenges in utilizing Information Systems and Information Technology (IS/IT) because it does not yet have a strategic plan that is not in accordance with and adequate to business needs and organizational goals. This study was conducted with the aim of improving the efficiency of data management and administrative services at the Pusomaen District Office. This study uses the Ward and Peppard methodology, which provides a comprehensive framework for formulating IS/IT strategies. Qualitative methods are applied through interviews, observations, and documentation studies. by conducting an analysis of the internal business environment (SWOT and Value Chain) and external (PEST and Five Forces Model). The McFarlan Strategic Grid is applied to evaluate the internal IS/IT environment. The results of the study produced a strategy in the form of an IS/IT roadmap for the next four years with a focus on infrastructure development, improving HR competencies, and IT-based data management. This planning is expected to improve the quality of service and operational efficiency at the Pusomaen District Office.Keywords: IS/IT Strategic Planning; Ward and Peppard; SWOT Analysis; IS/IT Rodmap; Pusomaen District Office AbstrakPada Penelitian ini membahas tentang Perencanaan Strategis Sistem Informasi dan Teknologi Informasi Menggunakan Meteodolgi Ward and Peppard pada Kantor Kecamatan Pusomaen. Kantor Kecamatan Pusomaen menghadapi tantangan dalam pemanfaatan Sistem Informasi dan Teknologi Informasi (SI/TI) karena belum memiliki perencanaan strategis yang belum sesuai dan memadai dengan kebutuhan bisnis dan tujuan organisasi. Penelitian ini dilakukan dengan tujuan untuk meningkatkan efisiensi pengelolaan data dan layanan administrasi pada kantor kecamatan Pusomaen. Penelitian ini menggunakan metodologi Ward and Peppard, yang menyediakan kerangka kerja komprehensif untuk merumuskan strategi SI/TI. Metode kualitatif diterapkan melalui wawancara, observasi, dan studi dokumentasi. dengan melakukan analisis lingkungan bisnis internal (SWOT dan Value Chain) serta eksternal (PEST dan Five Forces Model). McFarlan Strategic Grid diterapkan untuk mengevaluasi lingkungan SI/TI internal. Hasil penelitian menghasilkan strategis dalam bentuk roadmap SI/TI untuk empat tahun kedepan dengan difokuskan pada pengembangan infrastruktur, peningkatan kompetensi SDM, dan pengelolaan data berbasis TI. Perencanaan ini diharapkan meningkatkan kualitas layanan dan efisiensi operasional di Kantor Kecamatan Pusomaen.